Summary of Working Group 5: Physics with Heavy Flavours - Bhardwaj, V. (XXVII International Workshop on Deep-Inelastic Scattering and Related Subjects - DIS2019, 2019)
We present a summary of heavy-flavour physics at the the time of the DIS2019 conference. This summary is based upon the relevant plenary and parallel talks presented at the workshop. The summary is divided into four broad areas: (1) spectroscopy, (2) the production of b and c quarks in collisions, (3) top quark production and properties, and (4) b and c quark decay.
Only IISERM authors are available in the record.
Keywords: Heavy-flavour physics; Summary; Workshop